(untitled) (Swiss Medical Weekly, 2017)
Over the past two decades, hundreds of new somatic mutations have been identified in tumours, and a few dozen novel cancer therapeutics that selectively target these mutated oncoproteins have entered clinical practice. This development has resulted in clinical breakthroughs for a few tumour types, but more commonly patients’ overall survival has not improved because of the development of drug resistance. Furthermore, only a very limited number of oncoproteins, largely protein kinases, are successfully targeted, whereas most non-kinase oncoproteins inside cancer cells remain untargeted. Engineered small protein inhibitors offer great promise in targeting a larger variety of oncoproteins with better efficacy and higher selectivity. In this article, I focus on a promising class of synthetic binding proteins, termed monobodies, that we have shown to inhibit previously untargetable protein-protein interactions in different oncoproteins. I will discuss the great promise alongside the technical challenges inherent in converting monobodies from potent pre-clinical target validation tools to next-generation protein-based therapeutics.